2001
DOI: 10.1097/00005537-200109000-00028
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Laser Treatment in 244 Patients With Respiratory Papillomas

Abstract: Frequent and meticulously performed CO(2) laser excisions can achieve significant voice and airway improvement, and some clinical "cures." However, effective antiviral medicines and/or immunologic agents are needed to achieve true cures with elimination of all human papilloma virus 6 and 11 viruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(89 citation statements)
references
References 36 publications
1
82
0
5
Order By: Relevance
“…In one department the pulsed dye diode laser is used. The CO 2 laser has stood the test of time as one of the preferred surgical methods but is not without its problems, related to expense, risk of airway fire, delayed and collateral local tissue damage and the potential for HPV DNA particles aerosolization during the procedure [9,10]. The 585 nm pulsed dye laser has been reported as a safer alternative [11].…”
Section: Discussionmentioning
confidence: 99%
“…In one department the pulsed dye diode laser is used. The CO 2 laser has stood the test of time as one of the preferred surgical methods but is not without its problems, related to expense, risk of airway fire, delayed and collateral local tissue damage and the potential for HPV DNA particles aerosolization during the procedure [9,10]. The 585 nm pulsed dye laser has been reported as a safer alternative [11].…”
Section: Discussionmentioning
confidence: 99%
“…Six studies explored treatment of laryngeal papillomatosis in their cohort of patients [94,[97][98][99]106,113]. Five studies dealt specifically with tracheo-bronchial and pulmonary involvement [95,108,109,111,112] and were descriptive in nature.…”
Section: Lung Involvement In Rrp--the Cohort Studiesmentioning
confidence: 99%
“…Several authors have reported intermediate or long-term results of using C02 laser excision 16 or adjuvant therapies such as interferon alfa-Nl ,'? photodynamic therapy.t'' intralesional mumps vaccine, 19 or indole-Lcarbinol-" (Table 3 16 -2°) .…”
Section: Discussionmentioning
confidence: 99%